Time-of-day-dependent Sensitivity of the Reproductive Axis to RFamide-related Peptide-3 Inhibition in Female Syrian Hamsters - Gotlieb, Neta (J Neuroendocrinol, 2019)
In spontaneously ovulating rodent species, the timing of the luteinizing hormone (LH) surge is controlled by the master circadian pacemaker in the suprachiasmatic nucleus (SCN). The SCN initiates the LH surge through the coordinated control of two, opposing neuropeptidergic systems that lie upstream of the gonadotropin-releasing hormone (GnRH) neuronal system, the stimulatory peptide, kisspeptin, and the inhibitory peptide, RFamide-related peptide-3 (RFRP-3; the mammalian ortholog of avian gonadotropin-inhibitory hormone (GnIH)). We have previously shown that the GnRH system exhibits time-dependent sensitivity to kisspeptin stimulation, further contributing to the precise timing of the LH surge. To examine whether this time-dependent sensitivity of the GnRH system is unique to kisspeptin, or a more common mechanism of regulatory control, we explored daily changes in the response of the GnRH system to RFRP-3 inhibition. Female hamsters were ovariectomized to eliminate estradiol (E2) negative feedback and RFRP-3 or saline were centrally administered in the morning or late afternoon. LH concentrations and Lhβ mRNA expression did not differ between morning RFRP-3-and saline-treated groups but were markedly suppressed by RFRP-3 administration in the afternoon. However, RFRP-3 inhibition of circulating LH at the time of the surge does not appear to act via the GnRH system as no differences in mPOA Gnrh or RFRP-3 receptor Gpr147 mRNA expression were observed. Rather, RFRP-3 suppressed arcuate nucleus Kiss1 mRNA expression and potentially impacted pituitary gonadotropes directly. Together, these findings reveal time-dependent responsiveness of the reproductive axis to RFRP-3 inhibition, potentially via variation in the sensitivity of arcuate nucleus kisspeptin neurons to this neuropeptide.